2013
DOI: 10.1039/c3dt50233c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical interactions with Li+ and catalytic reactivity of electrochemically generated [FeICl(L)]2− and [CoI(L)]− complexes (L = salen or salophen)

Abstract: The cyclic voltammetric behavior of [FeIIICl(salen)] complexes has been investigated in CH3CN and compared to that obtained with [CoII(salen)] analogues. Details of the mechanism associated with iron- and cobalt-salen complex reduction in the presence of the lithium cation have been elucidated by comparison of simulated and experimental voltammograms. Electrogenerated [FeICl(salen)]²⁻ and [FeICl(salophen)]²⁻ complexes catalyze the dehalogenation of halo-alkyl compounds as is the case with [CoI(salen)]⁻ complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The CV trace of the mononuclear FeCl(L) (0.8 mm in acetonitrile with 0.1 m tetrabutylammonium tetrafluoroborate, Figure 1) displayed a first reversible cathodic process at E 1/2 = À 0.69 V vs Fc + /Fc (ΔE = 84 mV) attributed to the Fe III /Fe II couple, followed by a second, quasi-reversible one at E 1/2 = À 2.00 V vs Fc + /Fc, and attributed to reduction of Fe II to Fe I . [45] For Fe 2 (μ-O)(L) 2 the first, quasireversible cathodic wave encountered in the forward scan is cathodically shifted (E 1/2 = À 1.32 V vs Fc + /Fc, ΔE = 100 mV) and is attributed to the Fe III to Fe II reduction of both iron centers of the FeÀ OÀ Fe μ-oxo bridge. [49] The more negative potential required to reduce Fe III to Fe II in the dinuclear species with respect to the mononuclear one is in agreement with previous literature, [49] and was observed also for iron porphyrin analogs.…”
Section: Synthesis and Electrochemical Features Of Mononuclear And DImentioning
confidence: 97%
See 4 more Smart Citations
“…The CV trace of the mononuclear FeCl(L) (0.8 mm in acetonitrile with 0.1 m tetrabutylammonium tetrafluoroborate, Figure 1) displayed a first reversible cathodic process at E 1/2 = À 0.69 V vs Fc + /Fc (ΔE = 84 mV) attributed to the Fe III /Fe II couple, followed by a second, quasi-reversible one at E 1/2 = À 2.00 V vs Fc + /Fc, and attributed to reduction of Fe II to Fe I . [45] For Fe 2 (μ-O)(L) 2 the first, quasireversible cathodic wave encountered in the forward scan is cathodically shifted (E 1/2 = À 1.32 V vs Fc + /Fc, ΔE = 100 mV) and is attributed to the Fe III to Fe II reduction of both iron centers of the FeÀ OÀ Fe μ-oxo bridge. [49] The more negative potential required to reduce Fe III to Fe II in the dinuclear species with respect to the mononuclear one is in agreement with previous literature, [49] and was observed also for iron porphyrin analogs.…”
Section: Synthesis and Electrochemical Features Of Mononuclear And DImentioning
confidence: 97%
“…Salophen ligand is easily synthesizable from commercially available reagents; the idea of investigating its iron complexes for electrocatalytic reduction of CO 2 originated from previous observations in the literature. The electrochemical properties of FeCl(L) have been the subject of seminal research in the field of electrocatalysis by Bond and co-workers, [45] that identified sequential reduction of the Fe III center to Fe II and finally to Fe I , with this latter species being electrocatalytically active towards reductive dehalogenation of benzyl halides. [45] Furthermore, the analog cobalt(II) salophen complex was reported as a CO 2 -to-CO reduction electrocatalyst by Isse et al, [46] involving an electrogenerated cobalt(I) active intermediate.…”
Section: Rationalementioning
confidence: 99%
See 3 more Smart Citations